2018
DOI: 10.1186/s12870-018-1322-5
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and transcriptomic sequencing of Rosa hybrida provides microsatellite markers for breeding, flower trait improvement and taxonomy studies

Abstract: BackgroundRosa hybrida is a valuable ornamental, food and medicinal crop worldwide, but with relatively limited molecular marker resources, especially for flower-specific markers. In this study, we performed genomic and floral transcriptomic sequencing of modern rose. We obtained comprehensive nucleotide information, from which numerous potential simple sequence repeat (SSR) markers were identified but were found to have high rates of amplification failure and PCR product redundancy.ResultsWe applied a filteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…Potter et al [1] reported that the phylogenetic relationship between Fragaria and Rosa is closer than between Fragaria and Rubus. Qi et al [63] evaluated the SSR primer pairs using in silico PCR and demonstrated that strawberry is the closest to the rose followed by the raspberry. We found an interesting regularity in the size of alleles during cross-species amplification: alleles in Rubus species amplified using Fragaria primers had sizes similar to the expected, while alleles in Fragaria species amplified using Rubus primers were significantly smaller than expected.…”
Section: Choice Of Cultivars and Transferability Of Ssr Markersmentioning
confidence: 99%
“…Potter et al [1] reported that the phylogenetic relationship between Fragaria and Rosa is closer than between Fragaria and Rubus. Qi et al [63] evaluated the SSR primer pairs using in silico PCR and demonstrated that strawberry is the closest to the rose followed by the raspberry. We found an interesting regularity in the size of alleles during cross-species amplification: alleles in Rubus species amplified using Fragaria primers had sizes similar to the expected, while alleles in Fragaria species amplified using Rubus primers were significantly smaller than expected.…”
Section: Choice Of Cultivars and Transferability Of Ssr Markersmentioning
confidence: 99%
“…SSR markers, also known as microsatellite markers, are short tandem repeats of one to six nucleotides, which are widely distributed in coding and non-coding regions of the eukaryotic genome [ 18 ]. Over the past years, SSRs were successfully developed in different ornamental plants via data mining, such as Magnolia ashei [ 19 ], Lagerstroemia indica [ 20 ], Paeonia suffruticosa [ 21 ], and Rosa hybrida [ 22 ]. In addition, SSRs have also been widely used in plant genetics and breeding for genetic diversity analysis [ 23 ], cultivar identification [ 24 ], DNA fingerprinting [ 25 ], linkage mapping [ 26 ], and association mapping [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…viridulum Baker [27], crataegus Pinnatifida Bunge [28], Acer miaotaiense P. C. Tsoong [29], and Rosa hybrida hort. ex Lavalle [30]. Among the third-generation sequencing platforms, PacBio RS II, which is regarded as the first commercialized third-generation sequencer, is based on single-molecule real-time (SMRT) technology [31].…”
Section: Introductionmentioning
confidence: 99%